The Effectiveness Of Online-Based Learning: A Testament To English Language Learning - Khozinatul Ummatil Islamia (Advances In Social Humanities Research, 2023)
The development of information and communication technology in the era of Industry 4.0 has had a great influence on the teaching and learning process, This research is part of a series of classroom action research (three cycles) whose main focus is to identify the effectiveness of using web blogs in English language learning to improve students' ability to understand English texts. The description in this section is divided into two parts, namely the first part reveals research findings based on a comparison of data distribution and t-tests. While the second part is focused on discussing the relationship between the results of this research with related theories or previous research.